Short‐ and Long‐Term Effects of Adding Topical Cosmetics to a Dermatological Procedure (Thermage): A Randomized Controlled Comparative Study Exploring the Synergistic Effects - Park, Sae‐ra; Choi, Ji‐Yei; Suk, Jangmi; Suh, Byung‐Fhy; Kim, Eunjoo (Skin research and technology, 2025)
ABSTRACT Background Dermatological procedures improve skin changes caused by aging. However, few studies have focused on the effect of improving various skin characteristics compared with the concurrent use of cosmetics. We aimed to confirm changes in skin characteristics owing to anti‐aging dermatological procedures in the short‐ and long‐term and to determine the efficacy of the procedure when products with anti‐aging and repair effects are used together. Materials and Methods We included 42 women (mean age, 47.667 ± 3.183 years) divided into a test (n = 21) and control (n = 21) group, with no history of dermatological procedures within 3 months of the test participation date. The dermatological procedure involved a single application of Thermage treatments, and products containing repair and anti‐aging ingredients were used for the test group. The skin changes were assessed using device‐based measurements and image analysis up to 4 weeks post‐procedure. Results Post‐procedure side effects were alleviated 1 day after the procedure, and transepidermal water loss (TEWL) improved when the products were used together. Skin hydration, elasticity, density, fine lines, texture, and pores improved at 4 weeks after the procedure. When the test product was also used, the improvement was significantly greater, and TEWL of the face improved in the test group only. Aging‐related skin characteristics were improved by Thermage, and the combined use of test products and procedures with repair and anti‐aging effects improved skin characteristics. Conclusion Dermatological procedures and cosmetic products have internal and external anti‐aging effects on the skin, respectively, resulting in synergy.